TAFSSA stakeholder mapping: the agricultural market system and value chain in Bangladesh - Nur A Mahajabin Khan; Amitaksha Nag; Nandi, Ravi; Krupnik, Timothy J. (TAFSSA, 2024)
The network map presented here provides a high-level view of the stakeholder network within the agriculture market systems in Bangladesh. This is part of an effort to understand the networks at work within Bangladesh’s agricultural food system, encompassing integrated production, marketing, nutrition and climate subsystems. The lead question for this mapping exercise is: Who are the primary organizations, institutions and individuals in the public and private sectors that influence the sale and movement of crops, livestock and aquaculture products from farm to plate in Bangladesh? The following analysis uncovers the broader patterns of the drivers, barriers and gaps within the sub-system network, informing potential stakeholder interventions to bring about desired changes in the agrifood systems. Also, it will look into the fact that what can make better this network to achieve the expected result in terms of ensuring food security involving all the actors in their specific roles.